Vulnerability to Depression in Mothers of Emotionally and Physically Handicapped Children - Khan, Fouzia Naeem (JISR management and social sciences & economics, 2008)
In the present study, it was hypothesized that mothers of emotionally handicapped children will be more vulnerable to depression as compared to the mothers of physically handicapped children. In order to test these hypotheses, the Beck Depression Inventory (BDI) was given to 300 mothers. Sample was divided into 3 groups, 100 mothers of emotionally handicapped children, 100 mothers of physically handicapped children and 100 mothers of healthy children. Z-test was applied in order to get the statistical significance of the results. The results of the present study show that the mothers of emotionally handicapped children were more depressed than the mothers of physically handicapped children.